PENGARUH KEPEMILIKAN MANAJERIAL, THIN CAPITALIZATION, DAN CAPITAL INTENSITY TERHADAP TAX AVOIDANCE - Alma Widyaningsih (2022)
This study aims to determine the effect of managerial ownership, thin capitalization, and capital intensity on tax avoidance in 82 manufacturing companies listed on the Indonesia Stock Exchange for the 2018-2020 period. This research is a type of quantitative research using secondary data in the form of company annual reports. To analyze the data in this study, using the Fixed Effect model panel data regression using the STATA version 16 application. Based on the test resultsand analysis, it can be concluded that managerial ownership, thin capitalization, and capital intensity have no effect on tax avoidance.